BUILDING LITERACY AND NUMERACY IN MULTILINGUAL CLASSROOM: A CRITICAL REVIEW OF PEDAGOGICAL STRATEGY AND POLICY CHALLENGE IN TIMOR-LESTE - Salvador Magno Ximenes (International Journal of Teaching and Learning, 2025)
Literacy and numeracy are the competencies that facilitate lifelong learning, but their development is one of the major challenges in the multilingual setting, as happens in Timor-Leste. This paper represents a critical literature review, which synthesises current research, policy reports, and educational practices to investigate the barriers and opportunities to learn literacy and numeracy in primary schools. The results indicate that systemic limitations, language barriers between home and school languages, and a lack of pedagogical materials are barriers to successful learning. Specifically, the prevalence of Portuguese as the language of instruction has been known to interfere with early childhood learning among children, and the lack of teacher training leads to the worsening of inequalities in classroom performance. However, the review identifies new strategies that can boost student engagement and performance. The new strategies include mother tongue/translingual approaches, culturally responsive teaching, multiliteracies, and the incorporation of literacy and numeracy education in both local and social contexts. The evidence shows that literacy and numeracy are interdependent and that teacher professional development is conclusive. The review concludes that long-term development demands consistent language policies, an equal distribution of resources, and education for teachers. An inclusive, contextual approach can foster academic achievement and other wider objectives of equity and social cohesion within the education system in Timor-Leste.